2010
DOI: 10.1074/jbc.m110.119339
|View full text |Cite
|
Sign up to set email alerts
|

Intersubunit Hydrophobic Interactions in Pf1 Filamentous Phage

Abstract: Magic angle spinning solid-state NMR has been used to study the structural changes in the Pf1 filamentous bacteriophage, which occur near 10°C. Comparisons of NMR spectra recorded above and below 10°C reveal reversible perturbations in many NMR chemical shifts, most of which are assigned to atoms of hydrophobic side chains of the 46-residue subunit. The changes mainly involve groups located in patches on the interfaces between neighboring capsid subunits. The observations show that the transition adjusts the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…[11][12][13] Because LBs are a pathological hallmark of PD, extensive research has focused on the structural characterization of AS fibrils. [11][12][13][14][15][16][17][18] Magic-angle spinning solid-state nuclear magnetic resonance (ssNMR) spectroscopy has emerged as a powerful tool for the characterization of noncrystalline and insoluble proteins, 19 including membrane proteins, [20][21][22][23][24][25] oligomeric assemblies, [26][27][28][29][30][31] and amyloid fibrils. [32][33][34][35][36][37][38][39] Extensive studies on hAS fibrils using ssNMR revealed that the central fibril core extends at least from about residue Leu38 to about residue Val95 with mostly β-sheet secondary structure.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Because LBs are a pathological hallmark of PD, extensive research has focused on the structural characterization of AS fibrils. [11][12][13][14][15][16][17][18] Magic-angle spinning solid-state nuclear magnetic resonance (ssNMR) spectroscopy has emerged as a powerful tool for the characterization of noncrystalline and insoluble proteins, 19 including membrane proteins, [20][21][22][23][24][25] oligomeric assemblies, [26][27][28][29][30][31] and amyloid fibrils. [32][33][34][35][36][37][38][39] Extensive studies on hAS fibrils using ssNMR revealed that the central fibril core extends at least from about residue Leu38 to about residue Val95 with mostly β-sheet secondary structure.…”
Section: Introductionmentioning
confidence: 99%
“…McDermott's group showed the potential of MAS ssNMR to perform sequential assignment and secondary structure determination of the Pf1 phages [61]. Phase transition observed at T°~10°C was used to identify at a site-specific resolution residues involved in the subunit-subunit hydrophobic interfaces [62], leading to precious structural restraints to model the interfaces. High-resolution information can be extracted from 13 C/ 15 N labeled DNA in phages, as demonstrated for Pf1 [60], T7 [239] and fd [240] phages.…”
Section: Applications To Structural Investigations Of Bacterial Secrementioning
confidence: 99%
“…Protein samples ranging from micro- [28] to nano-crystals [29], fibrils [30,31], sedimented samples [32][33][34], membrane proteins embedded in lipids [35] to proteins in a physiological cellular environment [36], or attached to cellular components [37,38] can currently be investigated using multidimensional MAS ssNMR methods. Structural investigations on protein self-assemblies are increasingly reported such as on amyloids (functional [9,22,39] and deleterious [40][41][42][43][44][45][46][47][48][49][50][51]), prions [52][53][54][55][56][57][58][59], phages [25,[60][61][62], bacterial appendages [24,26,[63][64][65] and cytoskeleton filaments [7]. As shown in Fig.…”
mentioning
confidence: 99%
“…We describe the experimental approaches to NMR studies of capsid structure and dynamics, DNA packing and protein-DNA interactions, and discuss their outcomes. The results presented here are based on a series of publications from recent years [37][38][39][40][41][42][43][44][45] and some new insights into silver-doped fd phage particles. While this article discusses bacteriophage viruses, in recent years a variety of ssNMR techniques have been successfully applied to study structure and dynamics of HIV viral capsids [46,47] and most recently proton detected experiments combined with fast MAS were utilized to study measle-virus capsids [48], both of which have human hosts.…”
Section: Introductionmentioning
confidence: 99%